EFFECT OF SERVICE QUALITY AND CUSTOMER SATISFACTION ON EMPLOYEE PERFORMANCE AT PT. ASDP INDONESIA FERRY (PERSERO) - Fatari, Fatari; Maharani, Safrida; Hartoko, Gatot (Yayasan Education and Social Center, 2022)
This study aims to determine whether service quality and Consumer Satisfaction variables affect employee performance partially and simultaneously at PT. ASDP INDONESIA FERRY (Persero). This type of research uses a quantitative approach with associative methods. The population in this study as many as 300 people are employees of PT. ASDP Indonesia Ferry (Persero). The sampling technique used is the sampling technique using the incidental sampling technique and the determination of the number of samples using the Slovin formula, which is as many as 75 samples. The results showed that the value of t count could prove the quality of service influences employee performance. The value resulting from hypothesis testing for t count service quality is 3.918. It is known that the t- table value is 1.99300, because the t- count value is greater than t- table (t- count 3.918 > t- table 1.99300) with a sig value of 0.000 <0.05. Consumer satisfaction is a partially positive influence on employee performance, and it can be seen from the t value. The value resulting from hypothesis testing for t- count consumer satisfaction is 2.182. It is known that the value of the t table is 1.99300 because the value of the t count is greater than the t table (t count 2.182 > t table 1.99300) with a sig value of 0.032 < 0.05, Service quality and customer satisfaction both have an impact on employee performance. With a confidence level of 5% or 0.05 of the calculation results obtained value of F table at 3:12 of the calculation results obtained arithmetic value off 23,408, to determine the influence is there or not then do the comparison value f count = 23,408 > f table 3.12 with sig value 0.000 <0.05. For the coefficient of determination (R 2) of 0.394 or 39.4%. The study results concluded that partially or simultaneously, the quality of service and consumer satisfaction affected employee performance